2019
DOI: 10.1136/neurintsurg-2019-015410
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich emboli are associated with von Willebrand factor levels and have poorer revascularization outcomes

Abstract: Background and aimsPlatelets and von Willebrand factor (vWF) are key factors in thrombosis and thus are likely key components of acute ischemic stroke (AIS) emboli. We aimed to characterize platelet and vWF levels in AIS emboli and to assess associations between their expression levels and clinical and procedural information.Materials and methodHistopathological and immunohistochemical analysis of emboli collected as part of the multi-institutional RESTORE registry was performed. The composition of the emboli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 33 publications
1
60
2
Order By: Relevance
“…We did not observe significant CD42b-vWF presence in any of the serial sections from age- and sex-matched C57BL/6 mice although there were some sections that exhibited detectable CD42b-vWF (not shown). The presence of CD42b and vWF in a manner that appears to be extra/peri-vascular suggested that a substantial anomaly is occuring in the vascularization ( 61 66 ) of the non-endocrine tissue of NOD pancreata, at least in mice at 2 weeks of age. We proposed that any vascular anomaly would be reflected in an upregulation of P-selectin on the endothelium of these blood vessels.…”
Section: Resultsmentioning
confidence: 99%
“…We did not observe significant CD42b-vWF presence in any of the serial sections from age- and sex-matched C57BL/6 mice although there were some sections that exhibited detectable CD42b-vWF (not shown). The presence of CD42b and vWF in a manner that appears to be extra/peri-vascular suggested that a substantial anomaly is occuring in the vascularization ( 61 66 ) of the non-endocrine tissue of NOD pancreata, at least in mice at 2 weeks of age. We proposed that any vascular anomaly would be reflected in an upregulation of P-selectin on the endothelium of these blood vessels.…”
Section: Resultsmentioning
confidence: 99%
“…Increased levels of platelets and calcium may also render 'white' clots stiffer and impact the MT outcome. [14,17] However, despite the platelet-rich composition of 'white' clots compared to 'red' clots in our cohort, there was no signi cant difference in terms of number of passes during MT and nal modi ed Thrombolysis in Cerebral Infarction (mTICI) score.…”
Section: Discussionmentioning
confidence: 63%
“…We acknowledge that there are also other components in the platelets/other-rich areas identi ed by MSB so we performed immunohistochemistry to distinguish between platelets and platelet-related factors such as vWF. [14] The high expression of CD42b and vWF in our 'white' clots highlights their critical role in 'white' clots formation. Recent studies have described important histological features that may explain the recombinant tissue plasminogen activator (rtPA)-resistance of AIS thrombi: the presence of a dense outer shell containing mainly platelets, vWF and extracellular DNA as well as the presence in the plateletrich thrombi of dense brin structures lined with vWF, extracellular DNA and lled with platelets.…”
Section: Discussionmentioning
confidence: 97%
“…Platelet and von Willebrand factor (vWF) levels are useful additional hallmarks of clot composition. [24][25][26] Immunohistochemical staining for platelets (CD42b) and the vWF was performed on a Bond RX autostainer (Leica Biosystems). Antigen retrieval with Tris-EDTA was performed for platelet staining (anti-CD42b); no antigen retrieval was used for vWF staining.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Histologic quantification was performed on the digital slide using Image Analysis Software (Orbit; www.Orbit.bio) as described previously. 21,25 The percentage area of each component (RBC, WBC, fibrin, and platelet/other) within the clot was calculated for the histologic staining with MSB. 21 The percentage area of positive immunohistochemistry staining was calculated separately for CD42b and vWF.…”
Section: Imaging and Quantificationmentioning
confidence: 99%